Association Between Sleep Quality and Physical Fitness Among Practical and Non-Practical Anesthesiology Nursing Students at Aisyiyah University Yogyakarta - Fasya, Ricyta Islami; Rohmah, Astika Nur; Pambudi, Triyas Singgih (Adult Health Nursing Journal, 2025)
Introduction: Internship and non-internship students have different levels of busyness, internship students are busier than non-internship students, thus disrupting their sleep quality and physical fitness levels. In Indonesia, the prevalence of sleep disorders varies by age group, with sleep deprivation (<7 hours per night) reaching 64.7% in adolescents, around 38% of adolescents in urban areas and 37.7% in suburban areas of Indonesia experiencing sleep disorders. Objectives: To determine the relationship between sleep quality and physical fitness levels in internship and non-internship nursing students of Universitas Aisyiyah Yogyakarta . Methods : Quantitative research method with correlational analysis method through cross-sectional approach. The sample in this study amounted to 128 respondents, categorized as 64 internship anesthesiology nursing students and 64 non-internship anesthesiology nursing students , with simple random sampling technique by random method (drawing). Results: The results of the Spearman Rank test showed that sleep quality and physical fitness levels had a significant relationship with a p-value of 0.000 (p <0.05). The relationship between sleep quality and physical fitness levels in Anesthesiology Nursing Practice Students in the moderate category and Non-Practice in the strong category of Aisyiyah University with a positive (unidirectional) relationship . Conclusions : There is a significant relationship between sleep quality and physical fitness levels in Anesthesiology Nursing Practice and Non-Practice Students of Aisyiyah University Yogyakarta.